Impact of SARS-CoV-2 Infection on Cognitive Function: A Systematic Review - Alnefeesi, Yazen; Siegel, Ashley; Lui, Leanna M. W.; Teopiz, Kayla M.; Ho, Roger C. M.; Lee, Yena; Nasri, Flora; Gill, Hartej; Lin, Kangguang; Cao, Bing; Rosenblat, Joshua D.; McIntyre, Roger S. (Frontiers in Psychiatry, 2021)
The prevalence and etiology of COVID-19’s impact on brain health and cognitive functions is poorly characterized. With mounting reports of delirium, systemic inflammation, and evidence of neurotropism, a statement on cognitive impairment among COVID-19 cases is needed. A substantial literature has demonstrated that inflammation can severely disrupt brain function, suggesting the cytokine storm as a possible cause of neurocognitive impairments. In this light, the aim of the present study was to summarize the available knowledge of the impact of COVID-19 on cognition during the acute and recovery phases of the disease, in hospitalized patients and outpatients with confirmed COVID-19 status. A systematic review of the literature identified six studies which document the prevalence of cognitive impairment, and one which quantifies deficits after recovery. Pooling the samples of the included studies (total sample n=644) at three standards of quality produced conservative estimates of cognitive impairment ranging from 43.0-66.8% prevalence in hospitalized COVID-19 patients only, as. no studies which report on outpatients met criteria for inclusion in the main synthesis. The most common impairment reported was delirium and frequent reports of elevated inflammatory markers suggest etiology. Other studies have demonstrated that the disease involves marked increases in IL-6, TNFα, and IL-1β; cytokines known to have profound impacts on working memory and attention. Simultaneous impairment of these cognitive functions is a characteristic aspect of delirium, which suggests these cytokines as key players in the etiology of COVID-19 induced cognitive impairments. Clinicians are encouraged to assay inflammatory markers and cognitive functions at presentation to omit iatrogenic confounds from future analyses. Simultaneous impairment of these cognitive functions is a characteristic aspect of delirium, which suggests these cytokines as key players in the etiology of COVID-19 induced cognitive impairments. Clinicians are encouraged to assay inflammatory markers and cognitive functions at presentation to omit iatrogenic confounds from future analyses.